Ideologia e linguagem: a natureza social da linguagem - Oliveira, Sandra da Rocha M. de (Cadernos de Linguagem e Sociedade, 2010)
This paper has the purpose of supporting the thesis that language is a social fact and as such the appropriate locus for the construction and transmission of ideology. Two ways of understanding the term ’ideology’ are discussed, which, on one hand, enable viewing linguistic facts embedded in social practice, as indicated by the mediating function of ideology. On the other hand, the dissimulating function of ideology explains the connection of language with forms of power which are part of social structures.